2007
DOI: 10.1111/j.1472-765x.2007.02135.x
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid conversion by dairy bacteria cultured in MRS broth and buffalo milk

Abstract: Aims:  To evaluate strains of Lactobacilli, Bifidobacteria and Streptococci for their ability to produce conjugated linoleic acid (CLA) from free linoleic acid (LA). Methods and Results:  Eight dairy bacteria tolerant to LA were grown in MRS broth containing LA (200 μg ml−1) and CLA was assessed. Seven bacteria were able to form CLA after 24 h of incubation, varying percentage conversion between 17% and 36%. Lactobacillus casei, Lactobacillus rhamnosus, Bifidobacterium bifidum and Streptococcus thermophilus sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 26 publications
6
51
0
1
Order By: Relevance
“…2). Kim and Liu (2002) and Van Nieuwenhove et al (2007) reported similar observations for addition of non-fat dry milk powder into the fermentation medium. The proposed mechanism states that SM prevents CLA oxidation in addition to support better growth (Shantha and Decker 1993) and some of the milk proteins (a-and b-lactoglobulin) shielded the bacteria from LA toxicity effect.…”
Section: Uv-based Spectrophotometric Screening For Cla Productionsupporting
confidence: 63%
“…2). Kim and Liu (2002) and Van Nieuwenhove et al (2007) reported similar observations for addition of non-fat dry milk powder into the fermentation medium. The proposed mechanism states that SM prevents CLA oxidation in addition to support better growth (Shantha and Decker 1993) and some of the milk proteins (a-and b-lactoglobulin) shielded the bacteria from LA toxicity effect.…”
Section: Uv-based Spectrophotometric Screening For Cla Productionsupporting
confidence: 63%
“…So, microorganisms isolated from dairy products, human and animal intestine were demonstrated as CLA-producing bacteria, including lactic acid bacteria (LAB) and bifidobacteria. At the present, Lactobacillus reuteri, Lactobacillus rhamnosus, Lactobacillus plantarum; Lactobacillus brevis, Lactobacillus acidophilus; Lactococcus lactis, Propionibaterium freudenrehichii, Bifidobacterium sp, Streptococcus, among others, were able to form CLA [52][53][54].…”
Section: Bacterial Cla and Clna Productionmentioning
confidence: 97%
“…Here, L. casei, L. rhamnosus, and Strep. thermophilus showed the highest LA conversion in MRS broth, and increased two-or threefold in milk than MRS broth [53]. Strep.…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
See 2 more Smart Citations